Middleware Development for Heterogeneous Databases on Multi-Architecture Systems Small Medium Enterprise - Christopel H. Simanjuntak; Musfiah Musfiah; Muhammad Bahit; Cristovani W. Lohonauman; Stenly B. Dodie; Khamla Nonalinsavath (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2025)
The fisheries industry is highly complex, requiring information technology to support data recording, information management, and sales forecasting. At Kampunglawo, a sales information system has been developed to manage transactions and track shipments of fishery products. However, the sales forecasting systems were developed separately, with different architectures and underlying data structures, necessitating data duplication and restructuring and resulting in inefficiencies. The objective of this research is to develop an Application Programming Interface (API) that connects the two systems, enabling data sharing without redundancy. The methods used were literature review, system requirements analysis, design, implementation, functional and performance testing, and evaluation. The results of this research show that the developed API can synchronize data between the sales and forecasting systems with high efficiency. Testing showed that for 1, 10, and 50 synchronized data sets, the server response ratio was 1:1,057:1,869, with an increase in processing time of only 41.7% for the largest data volume. The conclusion of this research shows that using APIs can reduce processing time and eliminate the need for data restructuring, thereby increasing the efficiency of the company’sinformation system integration.